A survey on patients’ knowledge and expectations during informed consent for spinal surgery: can we improve the shared decision-making process? - Weckbach, Sebastian (Patient Saf Surg, 2016)
BACKGROUND: The informed medical consent in surgery requires to some point basic medical knowledge. The treating physicians while explaining the details and risks of the recommended procedure often imply this. We hypothesized, that patients do not have adequate medical understanding to decide about the ongoing therapy and its potential complications based on knowledge jeopardizing the patients’ safety. METHODS: We conducted a retrospective analysis of a prospective database using a multiple choice questionnaire with 10 basic questions about anatomy, clinical symptoms and therapies of spinal diseases in our spine clinic at a German university hospital. Included were all patients at the spine clinic who agreed to the study and to fill in the questionnaire. Furthermore the patients age, mother tongue, the past spinal surgical history, the length of duration of symptoms and the patients education were inquired. The data were analyzed descriptive. RESULTS: Included were 248 patients with an average age of 59 years (16–88 a). 70 % of all patients used German as their mother tongue. 30 % of the included patients already had spinal surgery and suffered on average for 13.4 years because of their spinal disorder. Overall 32.6 % of all questions were answered correctly (range 0.8–68 %). A correlation of correctly answered questions and the patients’ age, duration of symptoms, mother tongue, education and past surgical history could not be described. CONCLUSION: The percentage of correctly answered questions is almost as low as the likelihood of nearness in guessing. Having this in mind the patients do not choose any treatment option based on knowledge. The physicians need to provide more basic knowledge to the patients. This would increase the amount of successful therapies, content patients and the patients safety. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13037-016-0103-z) contains supplementary material, which is available to authorized users.